Analysis of children´s legal participation in judicial processes versus the recognition of the legal personality and superior interest manifistation´s (Revista de Investigaciones Universidad del Quindío, 2021)
This work presents an opinion on the right of children from formal logical definitions of the constitution of law, and application of the best interests of the child in processes of imparting justice, having as focus the recognition of their acts as transcendental protection and safeguard scheme, during and after legal proceedings, opting for a dogmatic scheme of new elements that from another perspective the figures of application of the law in children, as well as the legal effects that may arise in the work of the judge at the time of resolving in a specific case.
Keywords: Children's rights; best interests; due process; focus; dogmatic; judicial processes